Pengaruh Penggunaaan Aplikasi SIAP Terhadap Kinerja Pegawai Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia (BKPSDM) Kota Tanjungpinang - Fibri Novitasari; Novi Winarti; Ryan Anggria Pratama (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2024)
The SIAP application (Presence Activation Information System) has been implemented at the Personnel and Human Resources Development Agency since 2022. Although good attendance has been the first step, it also requires optimal bureaucratic performance as an effort to achieve institutional goals. The purpose of this study is to evaluate whether the use of the SIAP Application (Presence Activation Information System) has an influence on employee performance at the Personnel and Human Resources Development Agency (BKPSDM). This study used quantitative methods and involved the entire population, namely 38 employees of the Civil Service and Human Resources Development Agency. Data collection was carried out through distributing questionnaires to all BKPSDM employees as respondents, documentation and observation. The results of the analysis using the T test show that the significant value (0.002) is smaller than the probability of 0.05. Therefore, it can be concluded that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted, which means "The use of the SIAP application has an influence on employee performance (Y)." Although the SIAP Application Usage Variable (X) and the Employee Performance Variable (Y) are related, respondents' responses show some shortcomings related to the use of the SIAP Application (Presence Activation Information System), such as unstable network access constraints. Nevertheless, good attendance still has a positive effect on improving employee performance. Employee Performance Evaluation shows deficiencies in the indicators of Quality, Quantity, Timeliness, and Independence.